Resin composition, substrate, and copper clad laminate thereof
A resin composition with naphthalene epoxy resin, bismaleimide resin, crosslinker, polysiloxane, and silica filler addresses the thermal expansion mismatch, achieving low CTE and improved thermal stability for semiconductor substrates.
Patent Information
- Application Number
- JP2024048257
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-23
- Filing Date
- 2024-03-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The mismatch in thermal expansion coefficients between current resin substrates and semiconductor material silicon substrates, with resin substrates having a CTE of 4 ppm/°C to 8 ppm/°C, necessitates improvement for better material matching and stability.
A resin composition comprising naphthalene epoxy resin, bismaleimide resin, crosslinker, polysiloxane, and silica filler, with optional siloxane coupling agent, to achieve a CTE of less than 3 ppm/°C, enhancing thermal stability and dimensional stability.
The resin composition achieves a low CTE of less than 3 ppm/°C, providing better material matching, higher heat resistance, and optimal thermal stability with semiconductor material silicon substrates.
Smart Images

Figure 2025051576000001 
Figure 2025051576000002 
Figure 2025051576000003
Abstract
Description
[Technical field]
[0001] The present invention relates to resins, and in particular to resin compositions, substrates, and copper-clad laminates. [Background technology]
[0002] In recent years, with the development of 5G communication, copper clad laminate materials are being developed to achieve higher dimensional stability and lower expansion and contraction, so that the products have higher stability.
[0003] Furthermore, the difference between the thermal expansion coefficients of current substrates and the coefficient of thermal expansion (CTE) of semiconductor material silicon substrates, which is less than 2 ppm / ° C., creates problems in material matching.
[0004] In particular, the thermal expansion coefficient of a substrate made of a resin material is about 4 ppm / °C to 8 ppm / °C, which is far from the CTE of a silicon substrate made of a semiconductor material, and therefore there is still room for improvement. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention provides a resin composition for reducing the CTE of a substrate and a copper clad laminate made from the resin composition, thereby better matching the CTE of a semiconductor material silicon substrate, improving dimensional stability and providing a higher stability to the product. [Means for solving the problem]
[0006] The resin composition of the present invention includes a naphthalene epoxy resin, a bismaleimide resin, a crosslinker, an accelerator, and a filler.
[0007] In one embodiment of the invention, the filler comprises silica.
[0008] In one embodiment of the present invention, the resin composition comprises a polysiloxane.
[0009] In one embodiment of the present invention, the resin composition contains, relative to 100 parts by weight of the resin composition, 20% by weight to 70% by weight of a naphthalene ring epoxy resin, 20% by weight to 60% by weight of a bismaleimide resin, 10% by weight to 20% by weight of a crosslinking agent, 0.05 phr to 1.0 phr of an accelerator, and 50% by weight to 80% by weight of a filler.
[0010] In one embodiment of the present invention, the resin composition contains 0.5 phr to 2.0 phr of polysiloxane per 100 parts by weight of the resin composition.
[0011] In one embodiment of the present invention, the naphthalene ring epoxy resin comprises HP4710, HP9500, HP6000, NC7000L, NC7300, or a combination thereof.
[0012] In one embodiment of the present invention, the naphthalene ring epoxy resin has an epoxy equivalent of 170 g / eq to 250 g / eq.
[0013] In one embodiment of the invention, the bismaleimide resin comprises BMI1000, BMI2300, KI50P, KI70, or a combination thereof.
[0014] In one embodiment of the present invention, the polysiloxane comprises a polysiloxane diamine.
[0015] In one embodiment of the invention, the polysiloxane comprises HP2000, KF8012, FM3311, or a combination thereof.
[0016] In one embodiment of the present invention, the active hydrogen equivalent of the polysiloxane is 200 g / eq to 5000 g / eq.
[0017] In one embodiment of the invention, the silica is spherical.
[0018] In one embodiment of the present invention, the average particle size (D50) of the silica is from 25 nm to 1.5 μm.
[0019] In one embodiment of the invention, the silica comprises a silica having a first average particle size (D50), a silica having a second average particle size (D50), a silica having a third average particle size (D50), or a combination thereof.
[0020] In one embodiment of the present invention, the first average particle diameter (D50) is 0.5 μm to 1.5 μm, the second average particle diameter (D50) is 0.12 μm to 0.45 μm, and the third average particle diameter (D50) is 0.02 μm to 0.011 μm.
[0021] In one embodiment of the present invention, the resin composition may further include a siloxane coupling agent.
[0022] In one embodiment of the present invention, the siloxane coupling agent is 0.1 phr to 5 phr.
[0023] In one embodiment of the present invention, the resin composition has a coefficient of thermal expansion of less than 3 ppm / °C.
[0024] In one embodiment of the present invention, the resin composition has a coefficient of thermal expansion of less than 2 ppm / °C.
[0025] The substrate of the present invention comprises any one of the resin compositions.
[0026] The copper clad laminate of the present invention includes a first copper foil, a second copper foil, a glass fiber cloth located between the first copper foil and the second copper foil, and a resin. The resin is formed from a resin composition and is located within the glass fiber cloth.
[0027] In one embodiment of the invention, the fiberglass fabric comprises E-glass and S-glass.
[0028] In one embodiment of the invention, the resin can be impregnated into the fiberglass cloth through the resin composition and then baked to form the resin within the fiberglass cloth. Effect of the Invention
[0029] As described above, the resin composition, substrate, and copper-clad laminate provided by the present invention have a relatively low CTE, which may be less than 3 ppm / °C, or even less than 2 ppm / °C, and have properties such as better material matching with semiconductor material silicon substrates having a CTE of less than 2 ppm / °C, higher heat resistance, optimal thermal stability, and higher dimensional stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] Hereinafter, embodiments of the present invention will be described in detail. However, these embodiments are merely illustrative and do not limit the present invention.
[0031] In this specification, the amount of additive used is sometimes indicated in units of "phr." This is a term commonly used in the rubber compounding field and means parts by weight of additive per 100 parts by weight of rubber (parts per hundreds of rubber, phr).
[0032] The resin composition of the present invention includes a naphthalene ring epoxy resin, a bismaleimide resin, a crosslinking agent, a polysiloxane, an accelerator, and a filler, and may include a siloxane coupling agent to provide a resin with high dimensional stability. Each component will be described in detail below.
[0033] Naphthalene ring epoxy resin
[0034] The naphthalene ring epoxy resin may include HP4710 (DIC Corporation), HP9500 (DIC Corporation), HP6000 (DIC Corporation), NC7000L (Nippon Kayaku Co., Ltd.), NC7300 (Nippon Kayaku Co., Ltd.), or a combination thereof. The presence of two benzene rings can improve heat resistance, so that the resin has better stability under high temperatures.
[0035] The resin composition contains 20% by weight to 70% by weight of a naphthalene ring epoxy resin relative to 100 parts by weight of the resin composition. The epoxy equivalent of the naphthalene ring epoxy resin is 170 g / eq to 250 g / eq.
[0036] Bismaleimide Resin
[0037] One purpose of adding a bismaleimide resin is to improve the overall thermal stability of the resin. The bismaleimide resin may include BMI1000 (manufactured by Daiwa Chemical Industry Co., Ltd.), BMI2300 (manufactured by Daiwa Chemical Industry Co., Ltd.), KI50P (manufactured by KI Chemical Industry Co., Ltd.), KI70 (manufactured by KI Chemical Industry Co., Ltd.), or a combination thereof.
[0038] The resin composition contains 20% by weight to 60% by weight of a bismaleimide resin relative to 100 parts by weight of the resin composition.
[0039] Crosslinking Agent
[0040] The resin composition contains 10% by weight to 20% by weight of a crosslinking agent relative to 100 parts by weight of the resin composition.
[0041] Polysiloxane
[0042] Polysiloxane is a long-chain siloxane, and includes polysiloxane diamine. Polysiloxane can include HP2000 (Wacker Chemie), KF8012 (Shin-Etsu Chemical), FM3311 (JNC), or a combination thereof. HP2000 has a three-dimensional structure, while KF8012 and FM3311 are linear. The special microstructure of polysiloxane can be used to promote the dispersion of raw materials and reduce the coefficient of thermal expansion (CTE) of the substrate to 3 ppm / ℃ or less, and even 2 ppm / ℃ or less, so that the resin has high dimensional stability.
[0043] The resin composition contains 0.5 to 2 phr of polysiloxane per 100 parts by weight of the resin composition. The active hydrogen equivalent of the polysiloxane is 200 g / eq to 5000 g / eq.
[0044] The structures of HP2000, KF8012, and FM3311 all have the functional group -NH2, which can react with the epoxy structure of the naphthalene ring epoxy resin or the double bond structure of the BMI resin to improve the thermal stability of the reacted resin and reduce the CTE of the reacted resin. In addition, polysiloxane can also be regarded as a curing agent, so the long chain structure of polysiloxane can improve the dispersion of fillers such as silica.
[0045] Accelerator
[0046] The resin composition contains 0.05 phr to 1.0 phr of an accelerator for 100 parts by weight of the resin composition to accelerate the reaction.
[0047] Filler
[0048] The filler includes silica. The silica is spherical. The average particle size (D50) of the silica measured by a laser scattering particle size measuring device is 25 nm to 1.5 μm. The silica includes silica having a first average particle size (D50), silica having a second average particle size (D50), silica having a third average particle size (D50), or a combination thereof. The particle size can be assigned according to requirements. For example, to achieve a higher deposition density, two or three of the large particle size, medium particle size, and small particle size are selected. The first average particle size (D50) is about 0.5 μm to 1.5 μm, the second average particle size (D50) is about 0.12 μm to 0.45 μm, and the third average particle size (D50) is about 0.02 μm to 0.011 μm.
[0049] The resin composition contains 50% by weight to 80% by weight of a filler relative to 100 parts by weight of the resin composition.
[0050] Siloxane Coupling Agent
[0051] In addition to the naphthalene ring epoxy resin, the bismaleimide resin, the crosslinking agent, the polysiloxane, the accelerator, and the filler, the present invention can also include a siloxane coupling agent. In addition to increasing the dispersion between the raw materials like the polysiloxane, the siloxane coupling agent can also improve the adhesion between the resin and the copper foil after the reaction. For 100 parts by weight of the resin composition, the resin composition contains 0.1 phr to 5 phr of the siloxane coupling agent.
[0052] substrate
[0053] A resin formed using the resin composition can be used to form a substrate.
[0054] Copper Clad Laminate
[0055] The resin formed using the resin composition can be used in a copper clad laminate. The copper clad laminate includes a first copper foil, a second copper foil, a glass fiber cloth located between the first copper foil and the second copper foil, and a resin. The resin is formed from the resin composition and is located within the glass fiber cloth.
[0056] The fiberglass cloth can include fiberglass cloths having different properties, such as E-glass and S-glass.
[0057] The resin formed from the resin composition located within the fiberglass cloth can be formed by immersing the fiberglass cloth in the resin composition and then baking or otherwise treating to form the resin within the fiberglass cloth.
[0058] Preparation method
[0059] First, the resin composition including naphthalene epoxy resin, bismaleimide resin, crosslinker, polysiloxane, accelerator, filler, and other raw materials was stirred and mixed, and if necessary, dispersed and mixed using a high-speed homogenizer to obtain a formulation solution.
[0060] The fiberglass fabric is then immersed in the formulation solution and then baked or otherwise treated.
[0061] Next, the glass fiber cloth soaked in the formulation solution and the copper foil were combined and processed through a hot press to obtain a copper foil substrate.
[0062] Finally, the copper foil was removed by a chemical method to obtain a substrate made of the resin composition according to the present invention.
[0063] Examples and Comparative Examples
[0064] Considering different experimental themes, the present invention uses the following blending ratios of each resin composition and uses the substrates made by the preparation methods to carry out a series of characteristic analysis tests as shown in the following table.
[0065] The glass transition temperature (° C.) was tested by a dynamic mechanical analyzer (DMA).
[0066] Water absorption rate (%): After heating in a pressure cooker at 120°C and 2 atmospheres for 120 minutes, the weight change before and after heating is calculated.
[0067] Heat resistance: The test specimen was heated at 120°C in a pressure cooker at 2 atm for 120 minutes, then immersed in a soldering furnace at 288°C and observed. If there was no delamination, the heat resistance was recorded as "OK".
[0068] Dielectric constant (Dk): The dielectric constant (Dk) is measured at a frequency of 10 GHz using an Agilent E4991A dielectric analyzer.
[0069] Dielectric loss tangent (Df): The dielectric loss tangent (Df) is measured at a frequency of about 10 GHz using an Agilent E4991A dielectric analyzer.
[0070] The coefficient of thermal expansion (CTE) was measured using a thermomechanical analyzer (TMA).
[0071] Peel strength (lb / in): A film was prepared from each resin composition, and the peel strength was measured using a universal tensile tester in accordance with IPC-TM-650 (2.4.8).
[0072] First, referring to Table 1 below, the following tests were carried out on the naphthalene ring epoxy resin, the BPA epoxy resin, and the BPF epoxy resin.
[0073] [Table 1]
[0074] The epoxy equivalent weights of BPA epoxy resin (product number L128, manufactured by Nanya Plastics Industry Co., Ltd.) and BPF epoxy resin (product number F170, manufactured by Nanya Plastics Industry Co., Ltd.) are 185 g / eq and 165 g / eq, respectively.
[0075] As shown in the results of Table 1, the CTE of Example 1 using naphthalene ring epoxy resin is 2.6 ppm / ℃, which is not only lower than the CTE of BPA epoxy resin of Comparative Example 1 (5.3 ppm / ℃) and the CTE of BPF epoxy resin of Comparative Example 2 (5.1 ppm / ℃), but also lower than the thermal expansion coefficient of the substrate made of the current resin material, which is 48 ppm / ℃ to 8 ppm / ℃, and more consistent with the CTE of the semiconductor material silicon substrate. It is clear that naphthalene ring epoxy resin is more effective than BPA epoxy resin and BPF epoxy resin.
[0076] Referring to Table 2 below, the effect of the presence of polysiloxane and the following tests were performed for different polysiloxanes.
[0077] [Table 2]
[0078] In Table 2, Examples 1-4 have the same blend ratios, except for the polysiloxane. Example 1 contains no polysiloxane, and Examples 2-4 contain 3.57 phr of the polysiloxanes HP2000, KF8012, and FM3311, respectively.
[0079] As the results in Table 2 show, the CTE of Example 1 is 2.6 ppm / °C, which is lower than the thermal expansion coefficient of 4 ppm / °C to 8 ppm / °C of substrates made of current resin materials, and is more consistent with the CTE of semiconductor material silicon substrates.
[0080] Furthermore, the CTEs of Examples 2 to 4 containing polysiloxane are 1.8 ppm / ° C., 1.9 ppm / ° C., and 1.9 ppm / ° C., respectively, all of which are less than 2 ppm / ° C. These CTEs are lower than the CTE of Example 1 not containing polysiloxane, and are closer to the CTE of the semiconductor material silicon substrate, providing optimal effects.
[0081] Referring to Table 3 below, the following tests were performed on different naphthalene ring epoxy resins.
[0082] [Table 3]
[0083] In Table 3, Examples 5 to 9 have the same blend ratio, except for the naphthalene ring epoxy resin used. The naphthalene ring epoxy resins used in Examples 2 to 6 are HP4710, HP9500, HP6000, NC7000L, and NC7300, respectively.
[0084] As the results in Table 3 show, the CTEs of Examples 5 to 9 were 2.6 ppm / °C, 2.8 ppm / °C, 2.7 ppm / °C, 2.9 ppm / °C, and 2.8 ppm / °C, respectively, which are lower than the thermal expansion coefficients of 4 ppm / °C to 8 ppm / °C of substrates made of current resin materials and are more consistent with the CTE of semiconductor material silicon substrates.
[0085] Referring to Table 4 below, the following tests were performed on different bismaleimide resins.
[0086] [Table 4]
[0087] In Table 4, Examples 10 to 13 have the same blending ratios, except for the bismaleimide resins used. The bismaleimide resins used in Examples 10 to 13 are BMI1000, BMI2300, KI50P, and KI70, respectively.
[0088] As the results in Table 4 show, the CTEs of Examples 10 to 13 are 2.9 ppm / °C, 2.8 ppm / °C, 2.7 ppm / °C, and 2.8 ppm / °C, respectively, which are lower than the thermal expansion coefficients of 4 ppm / °C to 8 ppm / °C of substrates made of current resin materials and are more consistent with the CTE of semiconductor material silicon substrates.
[0089] Referring to Table 5 below, the following tests were performed on different fiberglass fabrics.
[0090] [Table 5]
[0091] In Table 5, Comparative Examples 3 and 4 have the same compounding ratios, except for the type of glass fiber cloth used.
[0092] As the results in Table 5 show, the CTEs of Comparative Examples 3 and 4 were 5.6 ppm / °C and 2.6 ppm / °C, respectively, which are lower than the thermal expansion coefficient of 4 ppm / °C to 8 ppm / °C of substrates made of current resin materials and are more consistent with the CTE of semiconductor material silicon substrates.
[0093] As described above, the resin composition, substrate, and copper-clad laminate provided by the present invention have a relatively low CTE, which may be less than 3 ppm / °C, or even less than 2 ppm / °C, and have properties such as better material matching with semiconductor material silicon substrates having a CTE of less than 2 ppm / °C, higher heat resistance, optimal thermal stability, and higher dimensional stability. [Industrial Applicability]
[0094] The resin composition, substrate, and copper-clad laminate provided by the present invention can be applied for higher heat resistance, optimal thermal stability, and higher dimensional stability.
Claims
1. A naphthalene ring epoxy resin; A bismaleimide resin, A cross-linking agent; A promoter; A filler; A resin composition comprising:
2. The resin composition according to claim 1 , wherein the filler comprises silica.
3. The resin composition according to claim 1 , further comprising a polysiloxane.
4. The resin composition comprises, for 100 parts by weight of the resin composition, 20% by weight to 70% by weight of the naphthalene ring epoxy resin; 20% to 60% by weight of the bismaleimide resin; 10% to 20% by weight of said crosslinker; 0.05 phr to 1.0 phr of said accelerator; 50% to 80% by weight of said filler; The resin composition according to claim 3 .
5. 5. The resin composition of claim 4, wherein the resin composition further comprises 0.5 phr to 2.0 phr of the polysiloxane per 100 parts by weight of the resin composition.
6. 2. The resin composition of claim 1, wherein the naphthalene ring epoxy resin comprises HP4710, HP9500, HP6000, NC7000L, NC7300, or a combination thereof.
7. 2. The resin composition according to claim 1, wherein the naphthalene ring epoxy resin has an epoxy equivalent of 170 g / eq to 250 g / eq.
8. 2. The resin composition of claim 1, wherein the bismaleimide resin comprises BMI 1000, BMI 2300, KI 50P, KI 70, or a combination thereof.
9. The resin composition according to claim 3 , wherein the polysiloxane comprises a polysiloxane diamine.
10. 4. The resin composition of claim 3, wherein the polysiloxane comprises HP2000, KF8012, FM3311, or a combination thereof.
11. 4. The resin composition according to claim 3, wherein the active hydrogen equivalent of the polysiloxane is from 200 g / eq to 5000 g / eq.
12. The resin composition according to claim 2 , wherein the silica is spherical.
13. The resin composition according to claim 2, wherein the average particle diameter (D50) of the silica is 25 nm to 1.5 μm.
14. 3. The resin composition of claim 2, wherein the silica comprises a silica having a first average particle size (D50), a silica having a second average particle size (D50), a silica having a third average particle size (D50), or a combination thereof.
15. The first average particle diameter (D50) is 0.5 μm to 1.5 μm, the second average particle diameter (D50) is 0.12 μm to 0.45 μm, and the third average particle diameter (D50) is 0.02 μm to 0.011 μm. The resin composition according to claim 14.
16. The resin composition of claim 1 further comprising a siloxane coupling agent.
17. The resin composition according to claim 16, wherein the siloxane coupling agent is from 0.1 phr to 5 phr.
18. The resin composition according to claim 1, wherein the resin composition has a thermal expansion coefficient of less than 3 ppm / °C.
19. A substrate comprising the resin composition of claim 1.
20. A first copper foil; A second copper foil; a glass fiber cloth located between the first copper foil and the second copper foil; A resin formed from the resin composition of claim 1 and located within the glass fiber cloth; A copper clad laminate comprising:
21. 21. The copper clad laminate of claim 20, wherein the fiberglass cloth comprises E-glass and S-glass.
22. 21. The copper clad laminate of claim 20, wherein the resin is formed within the glass cloth by soaking the glass cloth in the resin composition and then baking.
Citation Information
Patent Citations
Resin composition, prepreg, laminated board, multilayer printed wiring, and semiconductor device
JP2011026419A
Resin composition, prepreg, laminate, and printed wiring board
JP2014084327A
Thermosetting resin composition, prepreg, film with resin, laminate, multilayer printed bord and semiconductor package
JP2017114964A
Molding material for sealing and electronic part device
JP2017165921A
Resin film for interlayer insulating layer, laminate, printed wiring board, semiconductor device, and method of manufacturing laminate
JP2019192343A